An analysis on the competitiveness of halal food industry in Malaysia: an approach of SWOT and ICT strategy - Abdul Manaf Bohari,; Cheng, Wei Hin; Nurwahida Fuad, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
The halal food industry is vital important to the world wide Muslims to ensure hygiene, cleanliness and not detrimental to their health and well-being in whatever they consume, use and purchase. Theoretically, halal is possible to be the benchmark for quality with specifically refers whatever is permitted by Syariah Islamiah and applies to every activity carried out by mankind. Practically, halal when used in relation to the business sector, it refers to business operation and conducted in a manner deemed permissible in Islam. Meanwhile, current development shows that the halal food industry has become one of important sectors that contributes to the societal development as well as it contributes to the national growth. The objective of the present paper is to analyze the competitiveness of business environment of halal food industry in Malaysia. The main method that used are PEST and SWOT analysis where each factors that are related to the halal food industry will be screened and evaluated of it importance. In addition, ICT-based strategy will be recommended on the halal food industry to enhance their current competitive forces as well as preparation for future challenges of the industry.